Influence of socioeconomic status in school age children within the Project Obesity Zero - Castro, Susana (2012)
Introduction: Childhood obesity is considered by the World Health Organization as a major public health concern of the XXI century. The socioeconomic status (SES), namely, household income, education and occupation of parents, has been strongly associated with childhood obesity. The purpose of this study is to evaluate the influence of SES in the nutritional status of school age children, within of the Project Obesity Zero (POZ). Methods: POZ is a quasi-experimental, multicentric study, developed in 2009 in five Municipalities of Portugal (Melgaço, Mealhada, Cascais, Beja and Silves) articulated with Healthcare Centres and local governments. The programme offered, to children and their families, a four stages intervention: 1) Individual Nutrition Counseling, 2) Healthy Cooking Workshop, 3) Children’s Group Sessions and 4) Parents/families Group Counselling. The criteria used to define nutritional status of children were the CDC Growth charts (2000). This criteria was adopted by the Portuguese Ministry of Health. Family SES was reported by families (POZ questionnaire). Descriptive analyses were evaluated. Differences between groups were tested using chi-square test. Crude odds ratio (OR) with 95% CI were calculated by univariate analysis and adjusted OR were calculated by multivariate logistic regression analysis. A P-value<0,05 level was considered statistically significant. Results: From the 293 children evaluated, 52% were female and 48% were male; 9,2% had normal weight, 37,9% were overweight and 52,9% were obese. 80,4% of the children decreased their BMI percentile and Mealhada was the municipality with the greater reduction (92,0%) (p<0,01). According to the present study, parents with an education level below the third cycle of basic education, unqualified occupations and household income higher than 500€/month, appear to be significant risk factors to increase BMI percentil on children. Conclusion: This study adds evidence to the eficacy of community-based projects on the prevention of childhood obesity, enphatizing the importance of SES variables in these interventions.